The impact of a naturalistic intervention on preschool children’s morphological awareness development - Rosa,João (2022)
Abstract This study evaluated the effectiveness of a morphological awareness intervention delivered by preschool teachers in the naturalistic setting of their classrooms. The participants were 162 Portuguese children, attending kindergarten who were allocated as groups to experimental and control conditions. The former group was the object of six-weeks morphological awareness intervention anchored on explicit discussions about the morphological structure of words appearing in selected storybooks. The control group received normal curriculum activities. Results showed strong to high effect sizes on morphological awareness post-test abilities of children in the experimental group related to identifying words of the same “family”, interpreting the meaning of stems and affixes in morphologically structured pseudowords and finding the base word in derived or inflected stimuli, after controlling for age, cognitive ability, vocabulary, pre-test phonological and morphological results. The relevance of developing tools that help preschool children to consciously manipulate morphemes as meaningful building blocks of words, in partnership with preschool teachers, is proposed.